Curators and sojourners in learning networks: Practices for transformation. (April 2019) - Risien, Julie
Highlights: Network planners can support transformation by embracing and leveraging complexity. Transformation emerges from a symphony of interdependent roles and practices. Practices that seem to counteract one another may actually occur in productive tension. Attention to a variety of network substructures and practices can enable innovative evaluation. Abstract: Networks are a promising mechanism for creating systemic change. Studies abound, but do not examine roles and practices to reveal the processes through which networks create transformative capacity. This participatory single case study provides a framework to examine structures, roles and practices. The framework details common network substructures, across which critical practices occur, and provides a typology of specific network practices of curators and sojourners . The primary claim is that a variety of structures and interdependent roles and practices work in concert to support transformation across sites and scales. Results have implications for network design, leadership, practice, and evaluation.